KONTRIBUSI PEMBERDAYAAN DAN KOMITMEN ORGANISASIONAL UNTUK MENINGKATKAN KINERJA ANGGOTA KOPERASI SETIA BHAKTI WANITA DI SURABAYA - I Made Bagus Dwiarta; - Suharyanto (Universitas Trunojoyo Madura, 2016)
This study aims to test and analyze organizational commitment to empowerment and contribution to improving the performance members Koperasi Setia Bhakti Wanita in Surabaya. This study uses the free variables i.e. organizational commitment and empowerment, as well as a bound variable performance.This study included in this type of research surveys that are used for the purpose of explanation or confirmatory, or also called research for testing hypotheses to explain the influences between variables or causal relationships between variables through hypothesis testing. A sample of these studies amounted to 150 respondents comprised the members of the Koperasi Setia Bhakti Wanita in Surabaya. Sampling techniques in the study was done by accidental sampling method. The data obtained through the distribution and collection of returned questionnaires and then analyzed using SPSS.A model of the relationships between the variables examined generating organizational commitment and empowerment that have important relationship against the performance members Koperasi Setia Bhakti Wanita in Surabaya. The results of this study also has important meanings especially for members Koperasi Setia Bhakti Wanita to the empowerment as a member of the cooperative organization and commitment Setia Bhakti Wanita to improve the members of Koperasi Setia Bhakti Wanita in Surabaya.